The Impact of Melaka as a UNESCO World Heritage Tourist Area on the Motivations - Ermansyah, Ermansyah; Sosiady, Mulia (InJEBA : International Journal of Economics, Business and Accounting, 2023)
Malays will not disappear from the world." The oath of Admiral Hang Tuah in the 15th century seemed to have received his "luck". When UNESCO designated Bandaraya Melaka as a World Heritage City on July 7, 2008, The aim of this research is to determine what factors influence the motivation of tourists visiting the Old City area of Bandaraya Melaka. The research methodology uses quantitative descriptive analysis with a sample size of 37 people. Variable (X1): psychological motivation has no effect on tourist motivation (Y), cultural motivation variable (X2) has no effect on tourist motivation (Y), social motivation variable (X3) has an effect on tourist motivation (Y), and fantasy motivation variable (X4) has an effect on tourist motivation (Y). The R2 value is 0.682, meaning that the influence of the independent variable on the dependent variable is 68.2%. While the remaining 31.8%, other variables amounting to 31.8 percent could be from medical treatment, costs, and travel services, which were not examined in this research.